Relative distribution of HPV genotypes in histological cervical samples and associated grade lesion in a women population over the last 16 years in Burgundy, France - Auvray, Christelle; Douvier, Serge; Caritey, Odile; Bour, Jean-Baptiste; Manoha, Catherine (Frontiers in Medicine, 2023)
Human papillomavirus is a predominant sexually transmitted viral pathogen. Our objective was to analyze the relative distribution of genotypes over time and to determine the genotypes associated with adverse clinical lesions.The study was based on data from adult women with cytological abnormalities from whom histological samples were obtained from 2005 to 2021. HPV genotyping was performed using PCR and INNO-LiPA assay (Fujirebio).Among the 1017 HPV-positive biopsies, 732 (72%) were infected with a single HPV genotype and 285 (28%) were infected with several HPV genotypes. Most of the infections involved the high-risk genotypes 16, 31 and 52. Throughout the study period, HPV 16 was the most encountered genotype (541, 53.2%), while HPV 18 was rather under-represented (46, 4.5%), especially in invasive cervical carcinoma. HVP52 (165, 16.2%) was detected mainly from 2008 to 2014, Such epidemiological data underlines the possibility of an emergence of a high-risk genotype.The most detected low-risk HPV in combination with high-risk HPV was HPV 54 in 6.5% of samples. Monoinfection by HPV16 led statistically more often to severe lesions than multiinfection involving HPV 16 (p<0.001), while multi-infections were significantly associated with severe lesions (p<0.001 for HPV 52, 31 or 33 ). HPV 16 was involved in 55.2% of high-grade lesions and in situ carcinoma and 76.3% of invasive carcinomas.In severe lesions, HPV 16 participation was predominant, whereas diverse genotypes were seen in low-grade lesions. Importantly, we observed that high-risk genotypes, for example HPV 52, can emerge for a few years then decrease even without vaccine pressure.